IMPACT OF ANTENATAL STEROID ADMINISTRATION ON NEONATAL RESPIRATORY OUTCOMES - HAQ , W; NAZ , N; TAJ , S; ARSH, .; BHITTANI , R (Biological and Clinical Sciences Research Journal, 2024)
The administration of antenatal steroids represents a pivotal intervention in obstetric care with profound implications for neonatal respiratory outcomes. The study's main objective is to find the impact of antenatal steroid administration on neonatal respiratory outcomes. This retrospective cohort study was conducted at Lady Reading Hospital Peshawar from July 2019 to June 2023. The study included all infants born at the hospital who met the criteria for preterm birth (gestational age less than 37 weeks). Maternal demographic information was extracted, encompassing maternal age, parity, and medical history. The data collection's primary focus was antenatal steroid administration, including the type of steroid used, dosage, and timing of the gestational age at delivery. Data was collected from 550 preterm infants. The mean maternal age in the antenatal steroid group was 28.5 ± 4.2 years, and 29.1 ± 4.5 years in the no antenatal steroid group. The mean gestational age was 32.2 ± 2.1 weeks and 31.8 ± 2.3, respectively, in both groups. In the antenatal steroid group (n=300), the majority received betamethasone (90.0%) compared to dexamethasone (10.0%). The timing of administration varied, with 16.7% receiving steroids before 28 weeks, 50.0% between 28-32 weeks, and 33.3% between 32-34 weeks. The mean dosage for betamethasone was 10.5 ± 2.3 mg, while dexamethasone had a mean dosage of 8.0 ± 1.5 mg. It is concluded that antenatal steroid administration was associated with a significant reduction in RDS incidence and a lower need for mechanical ventilation among preterm infants. These findings emphasize the clinical importance of timely antenatal steroid administration in improving neonatal respiratory outcomes.